Changes in the Parietal Lobe Subregion Volume at Various Stages of Alzheimer’s Disease and the Role in Cognitively Normal and Mild Cognitive Impairment Conversion - Fang Lu; Qing Ma; Cailing Shi; Wenjun Yue (Journal of Integrative Neuroscience)
Background: Volume alterations in the parietal subregion have received less attention in Alzheimer’s disease (AD), and their role in predicting conversion of mild cognitive impairment (MCI) to AD and cognitively normal (CN) to MCI remains unclear. In this study, we aimed to assess the volumetric variation of the parietal subregion at different cognitive stages in AD and to determine the role of parietal subregions in CN and MCI conversion. Methods: We included 662 participants from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, including 228 CN, 221 early MCI (EMCI), 112 late MCI (LMCI), and 101 AD participants. We measured the volume of the parietal subregion based on the Human Brainnetome Atlas (BNA-246) using voxel-based morphometry among individuals at various stages of AD and the progressive and stable individuals in CN and MCI. We then calculated the area under the curve (AUC) of the receiver operating characteristic (ROC) curve to test the ability of parietal subregions to discriminate between different cognitive groups. The Cox proportional hazard model was constructed to determine which specific parietal subregions, alone or in combination, could be used to predict progression from MCI to AD and CN to MCI. Finally, we examined the relationship between the cognitive scores and parietal subregion volume in the diagnostic groups. Results: The left inferior parietal lobule (IPL)_6_5 (rostroventral area 39) showed the best ability to discriminate between patients with AD and those with CN (AUC = 0.688). The model consisting of the left IPL_6_4 (caudal area 40) and bilateral IPL_6_5 showed the best combination for predicting the CN progression to MCI. The left IPL_6_1 (caudal area 39) showed the best predictive power in predicting the progression of MCI to AD. Certain subregions of the volume correlated with cognitive scales. Conclusion: Subregions of the angular gyrus are essential in the early onset and subsequent development of AD, and early detection of the volume of these regions may be useful in identifying the tendency to develop the disease and its treatment.